A large elevation in 15N/14N of collagenous amino acids: an insight from starvation experiments of marine organisms - Hyuntae Choi; Yuko Takizawa; Nayeon Park; Yoshito Chikaraishi (Progress in Earth and Planetary Science)
Abstract Nitrogen isotope ratios of amino acids (δ15NAA) have widely been employed as a powerful tool for estimating the trophic position of organisms in food webs. This estimation is based on an elevation pattern in the δ15NAA value, a large elevation for the trophic amino acids (e.g., 8.0‰ for glutamic acid) while a little elevation for the source amino acids (e.g., 0.4‰ for phenylalanine), associated with the deamination of amino acids in consumers. However, several elevation patterns can be found in natural environments, one of which may be caused by the hydrolysis of specific protein under nutritional stress. In the present study, we identified ‘protein-specific elevation pattern’ for collagen, which connected to muscle tissues of fish and gastropods under nutritional stress. Time-series starvation for 45 days results in that collagen is consumed by 86% for the fish Girella punctata and by 50% for the gastropod Turbo sazae. Moreover, during the starvation, although a little change in the δ15NAA value is found in muscle fibers, a gradual elevation in the δ15NAA value is found in collagen for both trophic and source amino acids (e.g., by up to 11‰ for glutamic acid and up to 3‰ for phenylalanine, respectively, which can be explained by the Rayleigh fractionation model). We thus demonstrate that the consumption of collagen in organisms under starvation shows a unique elevation pattern in the δ15NAA value, which is consistent with the observation that collagen is degraded non-quantitatively by the collagenase reaction, whereas muscle is degraded quantitatively by the chaperone-mediated autophagy. The effect of δ15N elevation in all amino acids of collagen is negligible for G. punctata and diluted for T. sazae to the elevation in whole muscle tissue (i.e., = muscle fibers + collagen) even under long-term starvation, because the collagen proportion in the whole muscle is relatively small and is considerably decreased under the nutritional stress. Based on these results, we predict that the difference in the δ15NAA value between collagen and muscle fibers can be useful for evaluating the nutritional stress of fishes. However, great care will be required if studying food webs where collagen-rich organisms (i.e., gelatinous zooplankton) are abundant or if using collagen-rich materials in our studies.